Ovarian morphology and oogenesis of Leptodesmus dentellus (Diplopoda, Polydesmida, Chelodesmidae) - Zirondi, Márcia C. [UNESP]; Pinheiro, Tamaris G. [UNESP]; Fontanetti, Carmem S. [UNESP] (Brill Academic Publishers, 2013)
This study presents the ovarian morphology and the dynamics of the vitellogenesis process in the oocytes of the diplopod Leptodesmus dentellus. The oocytes are arranged in clusters called ovisacs which are distributed in pairs along the midline of the body forming the ovary. Regions similar to the germarium appear paired in the anterior region of the ovary; however, the development of the oocytes of this species does not follow a regionalisation in the reproductive organ. Cells in three developmental stages are found throughout the length of the ovary. Calcium, proteins, lipids and neutral polysaccharides were detected in the oocytes of L. dentellus. The polysaccharides and the proteins found in the oocytes have a double origin: endogenous, with the participation of the germinative vesicle, and exogenous, from follicular epithelium. The origin of the lipids is exogenous, i.e., they are incorporated into the oocytes, probably derived from the perivisceral fat body, which are highly developed in this region. The deposition of calcium is pre-vitellogenic and probably functions as a reserve during the juvenile stages. © 2012 Koninklijke Brill NV, Leiden.
Keywords: Histochemical analysis; histology; millipedes; vitellogenesis; arthropod; calcium; entomology; juvenile; lipid; morphology; polysaccharide; protein; reproductive biology